Time Management as a Key to Preventing Academic Procrastination: A Causal Analysis in High School Students - Nurul Huda; dini rakhmawati; Argo Widiharto (Universitas PGRI Yogyakarta, 2026)
Academic procrastination often becomes an obstacle that affects student achievement. This study aims to examine the effect of time management on academic procrastination among 11th-grade students at SMA Negeri 3 Demak. Using quantitative regression analysis within a correlational design, this study included all 11th-grade students from 12 classes (n=428) via total sampling. The results showed a strong negative correlation (r = -0.704, p < 0.001), with the regression equation Y = 103.887 – 0.911X indicating that each one-point increase in time management reduces procrastination by 0.911 points. Time management explains 49.6% of the variance in procrastination (R² = 0.496). In practice, these findings highlight the importance of equipping students with structured time management skills, which can improve learning outcomes, reduce stress, and prepare them to meet the increasing academic demands at higher levels of education. Given the urgency of academic procrastination as a widespread problem affecting students globally, this study emphasizes the need for schools to implement prevention strategies through guidance and counseling services. Keywords: time management, academic procrastination, student mental health, continuous learning, quality education